Pengaruh Penambahan Vortex Generator pada Bilah Taperless Turbin Angin - Kelvin Neco Mahendra Febriansya (Fakultas Teknik, 2025)
Wind turbine blades, designed with airfoil-shaped profiles, convert wind kinetic energy into mechanical energy. However, at high angles of attack (AoA), airflow tends to separate from the surface, causing a drop in aerodynamic efficiency. To counteract this, vortex generators (VGs) can be applied to the blade surface to induce localized turbulence, which energizes the boundary layer, delays flow separation, and maintains flow attachment along the airfoil. This research analyzes the impact of VG placement on the lift coefficient (Cl), drag coefficient (Cd), and lift-to-drag ratio (Cl/Cd) for the NACA 4412 airfoil. Simulations were performed using ANSYS Fluent with the k-omega SST turbulence model, under a freestream velocity of 6.75 m/s and a Reynolds number of 51,592. Rectangular VGs were installed at 20% of the chord length from the leading edge, with spacing variations of h5, h7, and h9. AoA variations included 0°, 4°, 8°, 12°, and 16°. Findings indicate that at low AoA (0°–8°), VG addition tends to reduce aerodynamic effectiveness—reflected by lower Cl and higher Cd compared to the baseline (no VG). Conversely, at high AoA (12° and 16°), VGs substantially improve performance. The optimal configuration, VG h7, achieved Cl = 1.2884, Cd = 0.2548, and Cl/Cd = 5.056. Flow visualization further revealed that, without VGs, significant flow separation occurred near the trailing edge at high AoA. In contrast, blades equipped with VGs—especially VG h7—exhibited enhanced flow stability and delayed separation, confirming the effectiveness of VG implementation in improving aerodynamic performance under critical flow conditions
Reupload file repositori 30 januari 2026_Kurnadi/Mita
Keywords: Vortex Generator; NACA 4412